A Review on Trademark and Its Enforcement Provisions under TRIPS (International Journal of Innovative Research in Computer Science & Technology, 2021)
The Agreement on Trade Related  Aspects of Intellectual Property Rights (TRIPS) for the  protection and promotion of Copyright Protection (IP)  rights in World Trade Organization member nations  includes trademark provisions (WTO). Implementation  and compliance with TRIPS trademarks and enforcement  clauses (15-21, 41-61) are two separate things, e.g.,  adoption of law and its application, therefore more work  is needed to ensure successful functioning of IP rights in  participating countries. TRIPS are really the only  intergovernmental organization with comprehensive  procedural safeguards for IP rights enforcement in  member states. This paper utilizes a qualitative study  approach to examine TRIPS rules dealing with  trademark and their enforcement processes (41-61) in  participating nations. Member nations' trademark  infringement mechanisms must be appropriate, timely,  and not difficult, exorbitant, or labor intensive. Signature  style enforcement procedures must also be based on due  process of the law and a fair trial, allowing accused  persons to sue for damages and compensatory damages  for losses suffered at the hands of infringement of  trademark, obtain injunctions to prevent future  encroachment, and punish fraudulent practices with long  prison sentences. TRIPS trademark and prosecution  clauses must be observed by participating nations due to  obstacles in administering enforcement requirements,  such as a paucity of IP expertise, IP professionals, vast  borders, a lack of resources, and so on. This must be  addressed out in effort to enhance and safeguard  reasonable trade activity in participating nations, a  protracted undertaking that must be accomplished by  beneficial initiatives in light of Weekends away  trademark and enforcement regulations.
Keywords: Intellectual Property; IP Rights; Trademark; Trade Related; World Trade Organization